2017
DOI: 10.1007/s10517-017-3704-3
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effects of M1 Muscarinic Acetylcholine Receptor Agonist TBPB and α7n-Acetylcholine Receptor Activator GTS-21 on Mouse Mortality and Blood Concentration of Proinflammatory Cytokines in Sepsis

Abstract: Experiments on random-bred albino mice showed that M1 muscarinic acetylcholine receptor agonist (TBPB) and α7n-acetylcholine receptor agonist (GTS-21) significantly reduced mortality of mice with experimental sepsis (intraperitoneally administration of E. coli) in 4 and 24 h after modeling by reducing blood concentration of proinflammatory cytokines TNF-α, IL-1β, and IL-6. Combined treatment with TBPB and GTS-21 determined their additive effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 12 publications
0
29
0
Order By: Relevance
“…OPC acute intoxication of decreased the TNF-α, IL-1β and IL-6 blood concentrations after sepsis modeling compared to the control group (sepsis without the use of drugs). Numerous studies have shown that the established effects are associated with acetylcholine m1AChRs activation of the brain, 18,21 α7nAChRs of MMS cells, nAChRs of adrenal medulla and other mechanisms. [9][10][11]14,16,17,19 The implementation of the reduction of pro-inflammatory cytokines TNF-α, IL-1β, IL-6, and others (the occurrence of anti-inflammatory effect) is provided by JAK2 kinase, STAT3 transcription factor, transcription factor NF-κB).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…OPC acute intoxication of decreased the TNF-α, IL-1β and IL-6 blood concentrations after sepsis modeling compared to the control group (sepsis without the use of drugs). Numerous studies have shown that the established effects are associated with acetylcholine m1AChRs activation of the brain, 18,21 α7nAChRs of MMS cells, nAChRs of adrenal medulla and other mechanisms. [9][10][11]14,16,17,19 The implementation of the reduction of pro-inflammatory cytokines TNF-α, IL-1β, IL-6, and others (the occurrence of anti-inflammatory effect) is provided by JAK2 kinase, STAT3 transcription factor, transcription factor NF-κB).…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11]14,16,17,19 The implementation of the reduction of pro-inflammatory cytokines TNF-α, IL-1β, IL-6, and others (the occurrence of anti-inflammatory effect) is provided by JAK2 kinase, STAT3 transcription factor, transcription factor NF-κB). 5,10,[15][16][17][18][19] In addition, the decrease in mortality from sepsis after acute intoxication of OPC due to the suppression of the synthesis of proinflammatory cytokines is also associated with the effect of corticosteroids (activation of the hypothalamic-pituitaryadrenal system). 5,8,11…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…inflammatory pathway caused by the action of acetylcholine on α7n-acetylcholine receptors (α7nAChRs) cells of the monocytemacrophage system (MMC), followed by inhibition of the production by the cells of pro-inflammatory cytokines (TNF-α, IL-1β, IL-6) and reduced mortality from sepsis were devoted hundreds of articles various authors[12][13][14][15][16][17][18][19][20][21][22]. Reduced production of TNF-α, IL-1β, IL-6 (anti-inflammatory effect occurrence) for cholinergic anti-inflammatory pathway is provided kinase JAK2, transcription factor STAT3, NF-κB transcription factor)[14,[19][20][21][22][23].We have established on outbred mice that that acetylcholine chloride in a dose of 20 mg/kg 6 h after subcutaneous injection significantly reduces mortality of mice from sepsis induced by intraperitoneal injection of 2×10 9 CFUs diurnal culture of E. coli in 2.0 ml of saline and the blood levels of proinflammatory cytokines TNF-α, IL-1β, and IL-6 [18]. It was established in experiments on noninbred mice that activation of α7n-acetylcholine receptors (α7nAChR) by anabasine in single doses of 1.0 and 5.0 mg/kg for 2 h before modeling sepsis (intraperitoneal injection of 2×10 9 CFUs diurnal culture of E. coli) cause a significant dose-dependent reduction of mortality of mice due to a decrease in the amount of proinflammatory cytokines TNF-α, IL-1β and IL-6 in the blood.…”
mentioning
confidence: 99%